Sowing the oil: brutalist urbanism — Ciudad Guayana, Venezuela 1951-2012 - Brillembourg, Carlos (10º Seminário Docomomo Brasil, Curitiba, 2013, 2013)
Political, cultural and economic networks between the United States and Latin America from 1940-1990 stimulated the construction of large scale projects that were a testing ground for new urban and developmental theories. As a consequence of FDR’s “Good Neighbor Policy” to counter the Axis influence throughout Latin America, Town Planning Associates (Josep Lluis Sert and Paul Lester Weiner) were hired in Brazil in 1944 to design Ciudad dos Motores, a city dedicated to manufacturing tractors and airplanes. New principles of “Urban Design”, the concept of an urban core, were refined by Sert and Weiner together with the young Venezuelan architects Moises Benacerraf, Carlos Guinand when they were hired in 1951 by the Orinoco Mining Company (US Steel) to design two new industrial towns Puerto Ordaz and Ciudad Piar. In 1961 a larger scale of investment by Corporacion Venezolana de Guayana, modeled after the Tennesse Valley Authority, founded the new city of Ciudad Guayana and hired The Joint Center for Urban Studies of MIT and Harvard to work on a large scale regional plan that absorbed both Puerto Ordaz and the small colonial settlement of San Felix to form a new industrial city parallel to the Orinoco River. Like Buffalo, New York in its heyday, the new city of “Ciudad Guayana” on the Lower Orinoco valley of Venezuela combined good of river transportation with abundant hydroelectric power required for basic industries on the river and a “planned” new city for the workers and managers involved in the production of steel and aluminum products. This paper will show how three very different approaches to city building were applied in a short period of time: First, Sert’s urban core/patio “Heart of the City”, Second the Joint Center’s “Brutalist Urbanism” for a new linear city twenty miles long and Third,“Participatory Planning” in the 1990’s. Fifty years after its founding, Ciudad Guayana is a city of the approx.1,300,000 inhabitants still in search of a coherent identity.
Keywords: Brutalist Urbanism; Venezuela; Ciudad Guayana